Perceptions and Challenges Faced by Dental Students During Their Transition from Pre-Clinical to Clinical Training in the Conservative Department: A Cross-Sectional Study - Sumaya Aghila; Osama Sheneeb; Mohamed Hshad; Amal Kashelaf (AlQalam Journal of Medical and Applied Sciences, 2025)
A high level of stress among dentistry students is attributable to the fact that they need to obtain multiple abilities, such as theoretical knowledge, practical competencies, and interpersonal skills. The purpose of this cross-sectional study was to examine the perspectives and obstacles that fourth-year dental students have as they shift to clinical practice in conservative dentistry. Data was collected during the academic year of November 2024- February 2025 among fourth-year dental students at Tripoli University, Libya, and responses were automatically recorded using a Google Forms questionnaire. The results showed that most students were anxious about starting their first case (74%). This anxiety was more evident in the conservative treatment cases (21.7%), while most preferred to work with patients in the middle age group (20 to 40) (74%) to reduce anxiety and preferred to work with first-degree relatives. The primary concern expressed by students was a fear of damaging the patient’s tooth (38.3%). There were also major problems with posture (33.2%) and handpiece use (29.8%). 47.2% of students expressed fear of unnecessary root canal treatment, while 43.8% were concerned about short-term filling failures. To reduce worry, 37% of students proposed the continual presence of supervisors, while 23.4% suggested higher work grades. Other suggested solutions included extending the preclinical phase (13.6%) and increasing case demonstrations (17.4%). The students were nervous about starting their first clinical cases, particularly the conservative ones. Most students appeared to be wary of working with children and the elderly, preferring to work with first-degree relatives. Their fear in the conservative area was that they might cause further damage to the tooth, such as requiring an unneeded root canal treatment, fracturing a filling, and needing to replace it, or exacerbating the patient’s exhausting pain. They also mentioned concerns about using the handpiece or not being able to see clearly due to their location. Initiatives such as enhanced supervisory support and prolonged preclinical training can assist with this transition.